2019
DOI: 10.1002/ccd.28159
|View full text |Cite
|
Sign up to set email alerts
|

Catheter‐based retrograde coronary sinus infusion is a practical delivery technique for introducing biological molecules into the cardiac system

Abstract: Objectives To demonstrate coronary sinus (CS) retrograde catheterization as a practicable technique for delivering biologics into the heart. Background There are many options to deliver biologics into the heart. However, there is no single optimal technique when considering safety, biologic retention, and reproducibility. Retrograde delivery has the potential to address many of these concerns. This study evaluated retrograde CS infusion of luciferase‐expressing plasmid in a porcine model using the Advance® CS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(24 reference statements)
0
2
0
Order By: Relevance
“… 29 Retrograde delivery via coronary sinus infusion has also been explored, with preclinical studies showing potential for plasmid delivery and retention over a significant range of injectate volumes. 30 Moreover, coronary sinus infusion has been evaluated in clinical studies of autologous bone marrow delivery for patients with both ischemic and nonischemic heart failure (HF). 23 This small clinical trial (60 patients) concluded that coronary sinus infusion is a safe delivery technique and that bone marrow treatment improved LV ejection fraction in both patient populations.…”
Section: Idmentioning
confidence: 99%
“… 29 Retrograde delivery via coronary sinus infusion has also been explored, with preclinical studies showing potential for plasmid delivery and retention over a significant range of injectate volumes. 30 Moreover, coronary sinus infusion has been evaluated in clinical studies of autologous bone marrow delivery for patients with both ischemic and nonischemic heart failure (HF). 23 This small clinical trial (60 patients) concluded that coronary sinus infusion is a safe delivery technique and that bone marrow treatment improved LV ejection fraction in both patient populations.…”
Section: Idmentioning
confidence: 99%
“…Unlike the obstructed coronary arterial system, the coronary venous system remains healthy and unobstructed, and thus has enormous potential for therapy delivery (Katti and Patil, 2012;Rodenberg et al, 2019), including retrograde delivery of arterial blood (Kassab et al, 1985). Although envisioned a century ago (Pratt, 1898;Beck and Stanton, 1948), therapeutic retroperfusion (a type of coronary sinus intervention), has not been adopted clinically because complicated equipment has been required to regulate perfusion to prevent damage to the coronary venous system when exposed to arterial pressures.…”
Section: Introductionmentioning
confidence: 99%